A survey on psychological distress and problematic smartphone use: two sides of the same coin?. (20th October 2021) - Covolo, L; Della Vedova, AM; Muscatelli, M; Loscalzo, Y; Giannini, M; Gelatti, U
Abstract: Background: Problematic smartphone use (PSU) is defined as a maladaptive smartphone use causing significant impairment in several areas of the individual and interpersonal functioning. Smartphones allow people to access the internet and social media at all times, providing the illusion of being in constant connection with the world. Literature has shown that maladaptive smartphone use is more frequent in young adults, and it is associated with psychological difficulties such as depression, anxiety, and feelings of tension and emotional discomfort, which can generally be referred to a condition of psychological distress. Aim: The aim of the study was to investigate the role of psychological distress and possible risk factors associated with PSU, as well as to evaluate the factor structure of the Smartphone Addiction Scale - Short Version (SAS-SV) test Italian translation in a sample of students. Methods: A sample of 2260 students (aged 18-25 years) filled in a web-based survey that included a sociodemographic questionnaire, also investigating time spent using smartphone and the preferred social media; the SAS-SV, the Internet Addiction Test and the Matthey Generic Mood Questionnaire were also part of the survey. Results: A multiple logistic regression analysis showed that moderate-high perception of psychological distress, time spent using smartphone overnight and during the day, education, and sex are independent predictors of potential smartphone addiction, as measured by the SAS-SV. An Exploratory Factor Analysis followed by a Confirmatory Factor Analysis showed a reliable two-factor structure of SAS-SV. Conclusions: The results of the study highlighted predictors that can be useful in prevention, confirming the impact of the extent of time spent using the smartphone, especially at night, and underlining the role of psychological distress in maladaptive smartphone use. Key messages: The findings raise concerns about the potential spread of smartphone addictive behaviour in Italian young adults. Perceiving a psychological distress condition was associated with potential smartphone addiction. It is important for prevention to have reliable screening tools that are quick and easy to fill out.